ANALISIS DETERMINAN YANG MEMPENGARUHI INDEKS PEMBANGUNAN MANUSIA (IPM) KABUPATEN SUMBAWA - Binar Dwiyanto Pamungkas; Novi Triana Dewi (Jurnal Ekonomi & Bisnis, 2022)
The purpose of this study was to examine the determinants that influence the human development index (HDI) of Sumbawa Regency which consists of economic growth and poverty on the HDI of Sumbawa Regency. This research is an associative research that aims to determine the relationship between two or more variables. The variables that will be studied in this study are economic growth and poverty as independent variables, and the IPM as the dependent variable. The type of data used is quantitative data obtained from documents and records that have been published by the Central Bureau of Statistics (BPS) of Sumbawa Regency. Researchers used documentation techniques to collect secondary data by finding and recording data related to research problems from documents and archives that have been published by the BPS of Sumbawa Regency. All data that has been collected will be processed using the SPSS program to be studied using techniques which include multiple linear regression analysis, individual hypothesis testing (t test), simultaneous hypothesis testing (F test), and determinant coefficient test (R2). The results of this study indicate that economic growth and poverty have a positive and significant effect on the HDI of Sumbawa Regency, both partially and simultaneously. The ability of the determinant variable that affects the HDI of Sumbawa Regency which consists of economic growth and poverty to variations in changes in the HDI of Sumbawa Regency is 95.9%, while the remaining 4.1% is influenced by other variables outside this research model, such as investment, employment, and politics.